Proyecto: desarrollo de un bioplástico a partir de residuos de cáscara de zapote a nivel laboratorio (2025)
This thesis focuses on obtaining a bioplastic using sapote peel as raw material, an agro-industrial waste rich in cellulose. The purpose was to develop a biodegradable material that can be a sustainable alternative to conventional plastic. To do this, various cellulose extraction and bioplastic production processes reported in research studies were analyzed, identifying the advantages and disadvantages of each method. Using the weighted factor selection matrix tactic and specific criteria, these processes were evaluated to select the most appropriate methods. The selected processes were divided into two main stages: In the first stage, acid hydrolysis was carried out with the aim of extracting cellulose, subjecting the peel to 98% hydrochloric acid and in the second, the cellulose is modified through an acetylation process, which involves the use of acetic acid, acetate anhydride and a sulfuric acid catalyst to produce the bioplastic (cellulose acetate).